Menelisik Pencegahan Pernikahan Usia Anak di Kota Surakarta - Giyartika; Nurhadi; Yuhastina (Faculty of Social Science, Universitas Negeri Malang, 2021)
This study aims to understand and explain efforts to prevent child marriage in Surakarta city in the study of population sociology. The areas sampled were five “Kampong KB” (Family Planning Villages) spread over five subdistricts in the city of Surakarta. Data were collected through in-depth interviews with 16 informants and structured interviews with 48 informants, consisting of Family Planning Instructors (PKB), Regional Family Planning Assistants (PPKBD), parents, teenagers and government officials. Data analysis was carried out in three stages, namely data reduction or the selection process, simplification, abstraction and transformation of raw data, then data presentation. Conclusions and verification are carried out continuously during the study. The results showed that in the effort to prevent the practice of child marriage in Surakarta city, there were several strategies implemented by various parties, namely Family Planning Instructors (PKB), Regional Family Planning Assistants (PPKBD) and government officials, so as to form a patterns of social interaction and evolutionary processes, also known as symbolic interactionism. The strategies that are carried out include taking a cultural approach, synergy of Activity Groups, enthusiasm for achievement, building interventions, commitment and consistency in running programs, maximizing the use of social media and orderly administration. Penelitian ini bertujuan untuk memahami dan menjelaskan upaya pencegahan pernikahan usia anak di Kota Surakarta dalam kajian ilmu sosiologi kependudukan. Wilayah yang dijadikan sampel adalah lima Kampung KB (Kampung Keluarga Berencana) yang tersebar di lima Kecamatan di Kota Surakarta. Data dikumpulkan melalui wawancara mendalam dengan 16 informan dan wawancara terstruktur dengan 48 informan, yang terdiri dari Penyuluh Keluarga Berencana (PKB), Pembantu Pembina Keluarga Berencana Daerah (PPKBD), orangtua, remaja dan aparatur pemerintah. Analisis data dilakukan melalui tiga tahapan, yakni reduksi data atau proses pemilihan, penyederhanaan, abstraksi dan transformasi data mentah, kemudian penyajian data. Penarikan kesimpulan serta verifikasi data dilakukan terus menerus selama penelitian berlangsung. Hasil penelitian menunjukkan bahwa dalam upaya pencegahan pernikahan usia anak di Kota Surakarta terdapat beberapa strategi yang dilakukan oleh berbagai pihak, yakni Penyuluh Keluarga Berencana (PKB), Pembantu Pembina Keluarga Berencana Daerah (PPKBD) dan aparatur pemerintah, sehingga terbentuk suatu pola interaksi sosial dan proses evolusioner atau yang dikenal dengan interaksionisme simbolik. Adapun strategi yang dilakukan diantaranya, melakukan pendekatan budaya, sinergisitas Kelompok Kegiatan (PokTan), semangat berprestasi, membangun intervensi, komitmen dan konsistensi menjalankan program, memaksimalkan penggunaan media sosial dan tertib administrasi.